Effect of Average Blood Glucose Greater Than 140 mg/dL on Adverse Patient Outcomes in Adult Medical/Surgical Patients - Morgan Wynes; Jaclyn Boyle (University of Minnesota Libraries Publishing, 2021)
Background: In hospitalized patients, hyperglycemia is defined as blood glucose greater than 140 mg/dL. Hyperglycemia can lead to the development of nosocomial infections as well as cardiovascular events.  Despite these risks, current guidelines recommend blood glucose be maintained between 140-180 mg/dL. Previous studies have shown that elevated blood glucose levels are associated with increased patient mortality. However, these studies assessed blood glucose at a single point in time. Objective: The primary objective of this study is to determine the impact of average blood glucose >140 mg/dL on a composite outcome of intensive care unit transfer, death, length of stay > 4 days, development of nosocomial infection, or new cardiovascular event (myocardial infarction [MI], ischemic stroke, deep vein thrombosis [DVT], pulmonary embolism [PE], or new onset heart failure) occurring during patient admission. Methods: This single centered, randomized, case-control, retrospective chart review sorted adult medical/surgical patients into two groups, average blood glucose ≤140 mg/dL or >140 mg/dL, of 120 patients each. Results: Forty-seven (39.2%) patients in the >140 mg/dL group experienced the primary composite outcome versus 27 (22.5%) patients in the ≤140 mg/dL group (p=0.005). Secondary outcomes found that patients with diabetes in the >140 mg/dL group were more likely to experience the primary outcome than those in the ≤140 mg/dL group (41 (48.8%) vs 3 (13.6%) p=0.003). Conclusions: This study found that medical/surgical patients with an average blood glucose >140 mg/dL may be at an increased risk of developing adverse patient outcomes.